Sirolimus use in allogeneic hematopoietic cell transplant recipients: assessing its senotherapeutic role in a high risk population - El Jurdi, Najla; ElHusseini, Heba; Cao, Qing; Klinger, Thomas; Shapiro, Ella; Cömert, Melike; Juckett, Mark; Holtan, Shernan G.; Yousefzadeh, Matthew J. (Frontiers in Aging, 2025)
Allogeneic hematopoietic cell transplantation (HCT) is often the only curative therapy for hematologic malignancies. Immune suppression is necessary for the engraftment of donor cells and prevention of graft-versus-host disease (GVHD). mTOR inhibitors like sirolimus are commonly used for GVHD prophylaxis. Low doses of sirolimus have demonstrated a gerotherapeutic effect, extending lifespan in animals, reducing senescent cell burden, and improving immune function in animals and humans. We hypothesized that the use of sirolimus in GVHD prophylaxis platforms, even at high doses, could have a senotherapeutic effect. We compared senescent cell burden in double umbilical cord blood HCT recipients with available baseline, day 100 and 365 post-HCT samples. All patients received an identical conditioning regimen with different GVHD prophylaxis: sirolimus + mycophenolate mofetil (MMF) or cyclosporine + MMF. At target doses to reduce GVHD risk, neither expression of senescence markers nor the abundance of SASP factors differed significantly in the sirolimus treated cohort compared to cyclosporine control cohort. However, we note a non-significant but perhaps biologically relevant trend of lower relative expression of p16INK4a and p21CIP1 post-HCT in the sirolimus cohort. Further longitudinal analysis including a larger cohort would be useful to determine the true magnitude of differences in senescent cell burden. Our results suggest that the daily administration and dosing used for GVHD prevention are less likely to confer clinical benefits, possibly indicating that the beneficial effects of sirolimus occur within a specific therapeutic window. These findings highlight the need to further investigate senotherapeutic approaches in this setting of accelerated aging.